Anne Frank's diary : the graphic novel - Polonsky, David; Folman, Ari (New York : Pantheon Books, 2018)
"The only graphic biography of Anne Frank's diary that has been authorized by the Anne Frank Foundation and that uses text from the diary--it will introduce a new generation of young readers to this classic of Holocaust literature. This adaptation of Anne Frank's Diary of a Young Girl into a graphic version for a young readership, maintains the integrity and power of the original work. With stunning, expressive illustrations and ample direct quotation from the diary, this edition will expand the readership for this important and lasting work of history and literature"--
Keywords: Frank, Anne, -- 1929-1945 -- Comic books, strips, etc; Jewish children in the Holocaust -- Netherlands -- Amsterdam -- Biography -- Comic books, strips, etc; Jews -- Persecutions -- Netherlands -- Amsterdam -- Biography -- Comic books, strips, etc; Amsterdam (Netherlands) -- Biography -- Biography -- Comic books, strips, etc; Biographies